Pengaruh Pembelajaran Video Pejuang (Penjumlahan dan Pengurangan) Berbasis Canva untuk Meningkatkan Hasil Belajar Siswa Kelas 2 SDN Klompang Timur 2 - Syahmi, Din Danish; Hardiansyah, Framz; Jamilah, Jamilah (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This study aims to assess the level of effectiveness of utilizing videos as Canva-based "Pejuang" learning media on the achievements of class II students of SDN Klompang Timur 2 who focus on addition and subtraction material. The type of approach method applied in this study applies a quasi-experimental method through a pre-test and post-test design, in order to spread the differences in learning outcomes before and after the application of learning videos. The results obtained from this study prove that the use of videos made with Canva is significantly able to optimize students' learning outcomes in mastering understanding of concepts in solving basic concepts of addition and subtraction. In addition, the use of this media also encourages increased student motivation and interest during the implementation of mathematics learning. This study makes a significant contribution to the world of education, because it shows that technology-based media can strengthen students' understanding of learning materials and become an innovative alternative for teachers in teaching mathematics in elementary schools. The implications of this research support the use of digital technology in education and provide a basis for developing curricula and educational policies that are more adaptive to technological developments.